Effect of Tillage Treatments of Hairy Vetch Residues on Soil Inorganic-N Distributions and Corn Growth in a Subtropical Region. (31st March 2020) - Anugroho, Fajri; Kitou, Makoto
Abstract : Conservation tillage has many advantages in crop production and weed control management. N-residue of hairy vetch as a green manure cover crop through tillage and no-tillage practices may increase inorganic-N level in soils and contribute to sustainable agriculture. Prior to corn cultivation, hairy vetch was cut after growing in the pots for 103 days. Six treated soils were prepared for no-tillage treatments (SRN, RN, and CN) and for tillage treatments (SRT, RT, and CT), where the soils were treated by shoot and root of hairy vetch residues, only root residues, and without application of hairy vetch as a control, respectively. Seeds of corn ( Zea mays L.) were sown and grown for 56 days after sowing. The shoot and root biomasses of corn under no-tillage were higher than those of tillage. Furthermore, the shoot biomass of corn in both SRN and SRT were higher than that in other treatments. The root biomass of corn was higher in upper layers (0–5 cm depth) and deeper layers (>10 cm depth) than in middle layers (5–10 cm depth) of soils. In the upper layer, the NH4 -N contents of no-tillage were higher at 9 and 23 DAT than those of tillage. The NH4 -N content of the soils for no-tillage in the middle layer and the deeper layer was lower than that of the CT treatment. The NO3 -N content of no-tillage in the middle and deeper layers was lower than that of CT at 23 and 65 DAT. N-uptake of corn in both no-tillage and tillage treatments with hairy vetch addition was higher than that of the control.